Protein kinase D1 in myeloid lineage cells contributes to the accumulation of CXCR3+CCR6+ nonconventional Th1 cells in the lungs and potentiates hypersensitivity pneumonitis caused by S. rectivirgula - Snyder, John D.; Yoon, Tae Won; Lee, Sangmin; Halder, Priyanka; Fitzpatrick, Elizabeth Ann; Yi, Ae-Kyung (Frontiers in Immunology, 2024)
Introduction Hypersensitivity pneumonitis (HP) is an extrinsic allergic alveolitis characterized by inflammation of the interstitium, bronchioles, and alveoli of the lung that leads to granuloma formation. We previously found that activation of protein kinase D1 (PKD1) in the lungs following exposures to Saccharopolyspora rectivirgula contributes to the acute pulmonary inflammation, IL-17A expression in the lungs, and development of HP. In the present study, we investigated whether PKD1 in myeloid-lineage cells affects the pathogenic course of the S. rectivirgula-induced HP. Methods Mice were exposed intranasally to S. rectivirgula once or 3 times/week for 3 weeks. The protein and mRNA expression levels of cytokines/chemokines were detected by enzyme-linked immunosorbent assay and quantitative real-time PCR, respectively. Flow cytometry was used to detect the different types of immune cells and the levels of surface proteins. Lung tissue sections were stained with hematoxylin and eosin, digital images were captured, and immune cells influx into the interstitial lung tissue were detected. Results Compared to control PKD1-sufficient mice, mice with PKD1 deficiency in myeloid-lineage cells (PKD1mKO) showed significantly suppressed expression of TNFα, IFNγ, IL-6, CCL2, CCL3, CCL4, CXCL1, CXCL2, and CXCL10 and neutrophilic alveolitis after single intranasal exposure to S. rectivirgula. Substantially reduced levels of alveolitis and granuloma formation were observed in the PKD1mKO mice repeatedly exposed to S. rectivirgula for 3 weeks. In addition, expression levels of the Th1/Th17 polarizing cytokines and chemokines such as IFNγ, IL-17A, CXCL9, CXCL10, CXCL11, and CCL20 in lungs were significantly reduced in the PKD1mKO mice repeatedly exposed to S. rectivirgula. Moreover, accumulation of CXCR3+CCR6+ nonconventional Th1 in the lungs were significantly reduced in PKD1mKO mice repeatedly exposed to S. rectivirgula. Discussion Our results demonstrate that PKD1 in myeloid-lineage cells plays an essential role in the development and progress of HP caused by repeated exposure to S. rectivirgula by contributing Th1/Th17 polarizing proinflammatory responses, alveolitis, and accumulation of pathogenic nonconventional Th1 cells in the lungs.